The History how State Scientific Library has Turned into Two State Public Scientific Technological Libraries: Chronical 1958 - A. L. Posadskov (Библиосфера, 2023)
The article is a documentary essay on the last stage of activity of the State scientific library of the USSR Ministry of Higher Education in 1957–1958 and the creation on its basis in 1958 of two largest modern scientific libraries in Russia. They are the State public scientific technological library of the Siberian branch of the Russian academy of sciences in Novosibirsk and the State public scientific technological library in Moscow. (At that time they were the State public scientific technological library of the Siberian branch of the USSR academy of sciences the State public scientific technological library of the USSR.) It is shown what stages of preparation and the decision implementation has gone through and what obstacles it has faced. The further development of the two State public scientific technological libraries has brought them to the forefront of information and library activities and has shown the correctness of the decision made in 1958.